FRI0398 Tenosynovitis and intratendineous tophi in GOUT: An extremity-dedicated MRI study of the hand and wrist. (23rd January 2014) - Piccazzo, R.; Revelli, M.; Paparo, F.; Aleo, E.; Barbieri, F.; Garlaschi, G.; Cimmino, M.A.
Abstract : Background: Tenosynovitis is a frequent condition in rheumatoid (RA) and psoriatic arthritis, but its frequence in gouty patients is not well known. In gout, it has been recently demonstrated in association with dactylitis (1). Objectives: To assess tendon involvement in patients with gout, evaluating hand and fingers by extremity-dedicated MRI. Methods: 30 patients with gout with (19 or 63.3%) or without (11 or 36.7%) previous arthritis of the wrist or hand were studied. Diagnosis was made on the basis of the ACR preliminary criteria (all patients) and by identification of MSU crystals in synovial fluid and/or tophi (26 patients). Twenty-four were men and 6 women; mean age was 67.1±14.3 years. MRI of the involved wrist and hand was performed with an extremity-dedicated, 0.2 T equipment (C-scan, ESAOTE, Genova, Italy). Sequences used included axial SE T2-weighted, axial and coronal STIR sequences, and Turbo-3D T1-weighted sequences on coronal plane with reconstruction on the other planes. This last sequence was repeated in 10 patients after intravenous gadolinium administration. A semi-quantitative scoring system for tenosynovitis developed for RA (2) was used in patients who were studied also after gadolinium infusion. In the remaining patients, an adaptation of the same score for the STIR sequence (3) was used. In the extensor tendons of the fingers, without synovial sheaths, peritendinitis was graded as present or absent. Results: Tenosynovitis was seen in 16/19 (84.2%) patients with hand and fingers arthritis and in 10/11 (90.9%) of those without (n.s.). Extensor tendons of the wrist were involved in 20/30 (66.7%) hands. Flexor tenosynovitis was seen in 16/30 (53.3%) hands. The corresponding figures at the finger level were 8/30 (26.7%) and 15/30 (50%), respectively. The compartments (wrist) and tendons (fingers) involved, together with the presence of tophi, are reported in table 1 . Conclusions: Tenosynovitis is present in 83.3% of patients with gout, when wrists and fingers are examined by MRI. It was more frequent in the extensor tendons at the wrist and in the flexor tendons at the fingers level. Tophi, both intra and peritendinous were more frequent in the fingers. Tendon involvement of the hand is a frequent feature of gout, also in patients without clinical involvement of the hand, suggesting that tendons are a preferential site of urate crystal deposition. References: Andracco R, Zampogna G, Parodi M, Paparo F, Cimmino MA. Dactylitis in gout. Ann Rheum Dis. 2010;69:316. Haavardsholm EA, Ostergaard M, Ejbjerg BJ, Kvan NP, Kvien TK. Introduction of a novel magnetic resonance imaging tenosynovitis score for rheumatoid arthritis: reliability in a multireader longitudinal study. Ann Rheum Dis. 2007;66:1216-20. Cimmino MA, Parodi M, Zampogna G, Barbieri F, Garlaschi G. Polymialgia rheumatica is associated with extensor tendon tenosynovitis but not with synovitis of the hands: a magnetic resonance imaging study. Rheumatology. 2011;50:494-99. Disclosure of Interest: None Declared